THE INFLUENCE OF CAPITAL STRUCTURE ON EARNING PER SHARE (EPS) - Utami, Eristy Minda; Hidayah, Riski Taufik (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purposes of this research are finding the influence of Capital Structure on Earning Per Share partially and simultaneously. The research method used is descriptive analysis verificative using secondary data. Statistic method is using multiple correlation regression statistic method to test the effect of indenpendent variables (capital structure) on the dependent variable (Earning Per Share) on Jakarta Islamic Index (JII) 2011 - 2016. Results of research using a significance level of 0.95 and 0.05 error rate indicates that the capital structure represented by the ratio of DAR has no effect on Earning Per Share (EPS), DER also has no effect on Earning Per Share (EPS), LDAR has a negative effect on EPS.